Virtual screening of the properties of a series of 5- arylidene derivatives of 3- (benzo[d]thiazol-2-ylamino)-2-thioxothiazolidin-4-one - Mosula , Liudmila; Kolodych, Iryna; Mosula , Viktoriia (Annals of Mechnikov's Institute, 2025)
Introduction. The importance of in silico analysis has been recognized due to the high reliability of predicted results. Virtual screening is based on the relationship between properties of a molecule and its structure. Certain online resources enable the prediction of a compound’s behavior in the human body by calculating important descriptors. The use of computer programs to calculate the physicochemical parameters of molecules, predict their pharmacokinetic properties, and assess "drug-likeness" is advantageous at the early stages of Drug Development, as it requires minimal time and financial investment. In molecular Drug Design, scientists are particularly interested in non-condensed bi- and polycyclic heterocycles, among which rhodanine derivatives with benzothiazole moeity demonstrate significant potential biological activity. To identify compounds with an optimal ADME (Absorption, Distribution, Metabolism, Elimination) profile, we selected 5-arylidene-substituted derivatives. The aim of the work was virtual screening and evaluation of the ADME properties of variously substituted 5-arylidene derivatives of 3-(benzo[d]triazol-2-ylamino)-2-thioxothiazolidin-4-one using the freely available SwissADME computer program. Materials and methods. The study materials included previously synthesized compounds (1–6) with pre-confirmed in vitro antitumor activity and virtually modeled derivatives (7–21) based on 3-(benzo[d]triazol-2-ylamino)-2-thioxothiazolidin-4-one. Methods: The research method is a freely available Swiss web tool SwissADME, hosted at http://www.swissadme.ch/. Results and discussion. A virtual design of a derivatives series and their screening was conducted. Comprehensive in silico studies made it possible to assess the potential of a structurally similar compounds. A range of physicochemical and pharmacokinetic parameters of the molecules, as well as their bioavailability (BS) and synthetic accessibility (SA), were determined. According to SwissADME predictions, most of the parameters are acceptable, which makes 5-arylidene derivatives interesting research targets. The similarity of the molecules to existing drugs was confirmed by their successful passage through the Lipinski filter. Sufficient bioavailability and synthetic accessibility of the derivatives are evidenced by calculated criteria (BS = 0.55; SA = 3.75–4.81). The least violations of optimal molecular descriptor values are predicted for compounds 1 and 7, while the greatest are for compounds 3, 6, and 18. The oral bioavailability of the molecules is limited by violations of two or more parameters, including saturation, polarity, lipophilicity, water solubility, size, and flexibility. Compound 7 is the most similar to those with high oral bioavailability. Brain penetration of the studied molecules is not expected, and low permeability through the skin is predicted (Log Kp from -3.53 to -6.10 cm/s). Most derivatives in the series (except compounds 19 and 21) are likely not P- glycoprotein substrates, which may contribute to their therapeutic efficacy, and selectively inhibit isoforms of cytochrome P450. Conclusions. The violations of some parameters of 5-arylidene-substituted derivatives are not critical according to modern Drug Design criteria. Overall, the predicted ADME profile of the compounds is acceptable. The molecular structures can be optimized, or alternative administration routes should be explored. The results of in silico predictions confirm the prospects for further research on this class of heterocycles, which are valuable for medicinal chemistry. Keywords: rhodanine, benzothiazoles, 5-arylidene derivatives, in silico screening, SwissADME.